Mechanisms of Persistence, Survival, and Transmission of Bacterial Foodborne Pathogens in Production Animals - Haiqi He (Frontiers Research Topics, 2018)
Foodborne illness resulting from food production animals is a global health concern, and the Centers for Disease Control estimate that one in six Americans will become sick with a foodborne illness each year. Of course there are numerous causes for these outbreaks, but contamination from a food production animal is certainly one source. Understanding the host-pathogen interaction and how foodborne bacterial pathogens establish a persistent infection and evade host immune responses will be pivotal in reducing the instance of foodborne illness traced back to a food production animal source. In this volume, we bring together original research and review articles covering some of the key issues surrounding the mechanisms of persistence, survival, and transmission of bacterial foodborne pathogens in production animals. The research focused on poultry and specifically addressed antibiotic resistance, Salmonella colonization, pathogen reduction strategies using pre- or probiotics, pathogen evasion, and post-harvest intervention and pathogen testing. The following 11 articles are fine examples of the multidisciplinary approaches that will be required to address and understand the complex interplay between food safety and animal production.